Contributions to Higher Engineering Education - Nascimento, Maria M.; Alves, Gustavo R.; Morais, Eva Virgínia Araújo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book focuses on teaching knowledge and principles (Higher Education) regarding professional practice of engineering (life and lifelong learning). It covers recent developments in engineering education. This book comprises the select proceedings of the conference organised by the Portuguese Society for Engineering Education. This book goes beyond the examination of the economic, culture, and social factors, which influence the education of engineers in different higher education institutions, and encompasses critical thinking and problem solving, communication, collaboration and creativity and innovation. These are essential components of engineering education. The contents of this book are useful to researchers and professionals engaged in the re-engineering of engineering education.
International Cooperation for Remote Lab use -- Mature learners' participation in higher education and flexible learning pathways: Lessons learned from an exploratory experimental research -- The flow of knowledge and level of satisfaction in engineering courses based on students' perceptions -- Innovative methodologies to teach materials and manufacturing processes in Mechanical Engineering -- "Learning by doing" Integrated Project Design in a Master Program on Product and Industrial Design -- The views of engineering students on creativity.
Keywords: Technology -- Sociological aspects; Technical education; Education and state; Science, Technology and Society; Engineering and Technology Education; Education Policy